2018
DOI: 10.1056/nejmoa1714678
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab plus Bortezomib, Melphalan, and Prednisone for Untreated Myeloma

Abstract: Among patients with newly diagnosed multiple myeloma who were ineligible for stem-cell transplantation, daratumumab combined with bortezomib, melphalan, and prednisone resulted in a lower risk of disease progression or death than the same regimen without daratumumab. The daratumumab-containing regimen was associated with more grade 3 or 4 infections. (Funded by Janssen Research and Development; ALCYONE ClinicalTrials.gov number, NCT02195479 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
619
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 797 publications
(682 citation statements)
references
References 26 publications
21
619
0
10
Order By: Relevance
“…These findings together suggest that the response with IMP may mature over a longer period compared with VMP and similar response rates can be achieved with IMP followed by ixazomib maintenance and VMP without maintenance. 17,19,23,33 It should also be noted that the weekly IMP regimen used at the RP2D was similar to the less-intense weekly VMP regimen used in the PETHEMA/GEM05 study, followed by bortezomib-based maintenance. 14 In the overall study, the CR rate post-VMP induction was 20%, 14 and in a matched-pairs analysis comparing the PETHEMA/GEM05 and VISTA regimens, the CR rate in PETHEMA/GEM05 patients improved from 19% post-induction to 30% overall, following maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings together suggest that the response with IMP may mature over a longer period compared with VMP and similar response rates can be achieved with IMP followed by ixazomib maintenance and VMP without maintenance. 17,19,23,33 It should also be noted that the weekly IMP regimen used at the RP2D was similar to the less-intense weekly VMP regimen used in the PETHEMA/GEM05 study, followed by bortezomib-based maintenance. 14 In the overall study, the CR rate post-VMP induction was 20%, 14 and in a matched-pairs analysis comparing the PETHEMA/GEM05 and VISTA regimens, the CR rate in PETHEMA/GEM05 patients improved from 19% post-induction to 30% overall, following maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,23 Most studies of the VMP regimen have utilized a fixed duration of treatment (often approximately 1 year) rather than extended or continuous therapy. 17,19,32,33 Furthermore, in the real-world clinical practice setting, early discontinuations due to toxicities are common. 34 As long-term, continuous therapy is associated with improved outcomes, 913 a tolerable, more convenient treatment regimen suitable for long-term use is needed, especially in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of daratumumab resulted in a 61% reduction in the risk of disease progression or death and an ORR of 83%. 18 Furthermore, registration studies of daratumumab are ongoing in high-risk, smoldering MM and light-chain amyloidosis, thereby exploring the potential of daratumumab across plasma cell dyscrasias. The investigators reported a 63% reduction in the risk of disease progression or death and an ORR of 93%.…”
Section: Discussionmentioning
confidence: 99%
“…Daratumumab is a first-in-class anti-CD38 monoclonal antibody approved for relapsed and refractory multiple myeloma[1,2] and being tested in both smoldering[3] and newly diagnosed myeloma[4]. CD38 is expressed on airway smooth muscle cells, and infusion related reactions (IRRs) were marked by symptoms (cough, wheezing, rhinorrhea) similar to those of allergic rhinitis.…”
mentioning
confidence: 99%